The Correlation between Parents' Support and the Students' Reading Ability during Pandemic (Scripta : English Department Journal, 2023)
This research aims towards (1) to discovery whether or not there is a correlation between parents’ support and the students’ reading ability during covid-19 pandemic at SMP Muhammadiyah Purworejo, Indonesia in the academic year 2020/2021 (2)to see whether there is or not correlation between parents’ support and the students’ reading ability during covid-19 pandemic at SMP Muhammadiyah Purworejo, Indonesia, Indonesia in the academic year 2020/2021. In this research, researcher used 60 students as a sample. The instrument which are used to obtain the data are questionnaire and test. Towards analyze the statistics the researchers using SPSS 16.0. The result shows the mean score of parents’ support is 68.78, and standard deviation score is 8.06. The mean score of test reading ability is 62.25 then standard deviation score is 6.47. The result of the correlation is -4.389, which means that the relationship between parents’ support and the students’ reading ability is opposite. Based on the result of this research it could be concluded that Ha is rejected and H0 is accepted, so there is no correlation between parents’ support and the students’ reading ability during covid-19 at SMP Muhammadiyah Purworejo, Indonesia, Indonesia in the  academic year 2020/2021.
Keywords: Correlations; Parents' support; Reading ability